HUBUNGAN INTENSITAS CAHAYA DAN JARAK PANCARAN SEBAGAI HUKUM KEBALIKAN KUADRAT - Zelviani, Sri (JFT: Jurnal Fisika dan Terapannya, 2018)
This research aims to determine the relationship between light intensity and beam distance as the inverse square law. From the experimental results it was found that the relationship between light intensity with the distance of the beam that is the farther the distance of the beam used, the intensity of the light obtained will be smaller, and vice versa. From the results of research conducted, obtained results for an average light intensity of 2.0636 Cd. Keywords: light intensity, beam distance, inverse square law